Development of a DNA microarray for species identification of quarantine aphids. Issue 12 (10th May 2013) - Lee, Won Sun; Choi, Hwalran; Kang, JinSeok; Kim, Ji‐Hoon; Lee, Si Hyeock; Lee, Seunghwan; Hwang, Seung Yong
Abstract: BACKGROUND: Aphid pests are being brought into Korea as a result of increased crop trading. Aphids exist on growth areas of plants, and thus plant growth is seriously affected by aphid pests. However, aphids are very small and have several sexual morphs and life stages, so it is difficult to identify species on the basis of morphological features. This problem was approached using DNA microarray technology . results: DNA targets of the cytochrome c oxidase subunit I gene were generated with a fluorescent dye‐labelled primer and were hybridised onto a DNA microarray consisting of specific probes. After analysing the signal intensity of the specific probes, the unique patterns from the DNA microarray, consisting of 47 species‐specific probes, were obtained to identify 23 aphid species. To confirm the accuracy of the developed DNA microarray, ten individual blind samples were used in blind trials, and the identifications were completely consistent with the sequencing data of all individual blind samples . CONCLUSION: A microarray has been developed to distinguish aphid species. DNA microarray technology provides a rapid, easy, cost‐effective and accurate method for identifying aphid species for pest control management. © 2013 Society of Chemical Industry